If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3a = 0 Solving 6 + 3a = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3a = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3a = 0 + -6 3a = 0 + -6 Combine like terms: 0 + -6 = -6 3a = -6 Divide each side by '3'. a = -2 Simplifying a = -2
| 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y | | (6xy+7)dx+(3x^2-2)dy=0 | | 6x+9-x+19= | | 4x+10=-42-8x | | 3n=34 | | 17x-2x=7x+11 | | 7x+13=3x+65 | | 4x+38=180 | | 2(x-3)(x-3)+3=13 | | 2(x-3)+3=13 | | x^4-x^3-2x^2+4x-24=0 | | (X^2+24)= | | 3x^2-11x-3=-x^2 | | Un=5+(0.1n-0.1) | | Un=5+(0.1n+0.1) | | Cos(5x)-cos(9x)=0 | | z^2-(3-2i)z+(5-5i)=0 | | 6x=n+4 | | 4x^2+12x+9=49x | | 4x^3+12x+9=49x | | -6.8(7.9+1.2*-7.3)+3.7=4.2*-7.3+40.90016 | | 1/8+2/3= | | 1/3+2/3= |